The COVID-19 experience of orthodontists in Jordan - Yana Sabbagh; Stephen M Chadwick; Benjamin R K. Lewis; Elham S Abu Alhaija (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVES: To understand the impact of the COVID-19 pandemic on orthodontic clinical services in Jordan. MATERIALS AND METHODS: Google Forms electronic questionnaires were distributed between March and June 2021 using the WhatsApp platform of the Jordanian Orthodontic Society and via direct WhatsApp messages. The survey was identical and contemporaneous to that used in the United Kingdom.[9] RESULTS: The survey yielded 127 unique responses, giving a response rate of 53.1%. The factors that had the greatest impact on service delivery were government guidance (78%), patients' fear of attending (70.1%), and increased cross-infection measures (65.4%). The survey revealed that there had been a perceived deterioration in oral hygiene (60.3%) and levels of compliance (61.9%) in patients in active treatment even though patients in treatment were prioritized during the pandemic. Also, 56.8% of respondents felt clinical staff should be vaccinated and undergo regular testing for COVID-19. Orthodontists within Jordan were optimistic regarding the speed at which clinical services would return to pre-pandemic levels of activity with 32.5% anticipating this would take less than 6 months. CONCLUSIONS: Patients in active orthodontic treatment, during COVID-19, have been prioritized but at the expense of new and review patients. Respondents in Jordan felt COVID-19 would have ongoing effects on clinical care, professional practice, and society. Most respondents supported the vaccination of orthodontic staff and were optimistic about the effect of a vaccination program on restoring clinical services.